2021
DOI: 10.3390/jof7121026
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids Specially Produced by Fungi: Structures, Biological Activities, Chemical and Biosynthesis (2015–2020)

Abstract: Fungi are widely distributed in the terrestrial environment, freshwater, and marine habitat. Only approximately 100,000 of these have been classified although there are about 5.1 million characteristic fungi all over the world. These eukaryotic microbes produce specialized metabolites and participate in a variety of ecological functions, such as quorum detection, chemical defense, allelopathy, and maintenance of symbiosis. Fungi therefore remain an important resource for the screening and discovery of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 168 publications
(207 reference statements)
0
25
0
1
Order By: Relevance
“…Previous research revealed that approximately 500 new sesquiterpenes, including about 20 new skeletons, were characterized from fungi during a five-year period (2015~2020) [ 14 ]. Soft coral-associated fungi are reported to be a rich source of sesquiterpenes.…”
Section: Terpenesmentioning
confidence: 99%
“…Previous research revealed that approximately 500 new sesquiterpenes, including about 20 new skeletons, were characterized from fungi during a five-year period (2015~2020) [ 14 ]. Soft coral-associated fungi are reported to be a rich source of sesquiterpenes.…”
Section: Terpenesmentioning
confidence: 99%
“…The sesquiterpenes form one of the richest groups of secondary metabolites in plant and fungal world; the C 15 structure allows many variations, which also causes the diversification of biological effects [ 8 ]. The name of the illudane type comes from the world of fungi, as similar molecules (illudin M and illudin S ( Figure 3 ) are the components of some poisonous mushroom species ( Omphalotus illudens, O. olearius ).…”
Section: Discovery Characterization and Properties Of The Moleculementioning
confidence: 99%
“…The name of the illudane type comes from the world of fungi, as similar molecules (illudin M and illudin S ( Figure 3 ) are the components of some poisonous mushroom species ( Omphalotus illudens, O. olearius ). The number of illudane-type sesquiterpenes described from mushrooms is increasing due to intensive research [ 8 ].…”
Section: Discovery Characterization and Properties Of The Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Our recent review indicated that fungal sesquiterpenoids usually have novel structures as well as significant biological activities. 2 Some of them have been used in clinical research as drugs or drug lead compounds. For instance, irofulven 3 is a semi-synthetic derivative of illudin S, a toxic sesquiterpene isolated from the mushroom Omphalotus illudens .…”
Section: Introductionmentioning
confidence: 99%